Bilateral Knee Synovial Osteochondromatosis: A Case Report - Nazia Naz S. KHAN; Rajaie NAMAS; Sally Jo SPERBECK; Harpreet SAGAR (Archives of Rheumatology, 2014)
Synovial osteochondromatosis or synovial chondrometaplasia is an uncommon benign condition involving large joints such as the knee, hip, and elbow characterized by proliferation of the synovium with cartilaginous metaplasia. In this article, we report an 85-year-old woman with bilateral knee pain and swelling secondary to bilateral synovial osteochondromatosis. The condition needs attention due to its high morbidity rates and although rare, malignant transformation can occur.